Child and Adolescent Multiple Victimization and/or Polyvictimization: A Portuguese Comparative Study - Ana Isabel Sani; Daniela Bastos; Maria Alzira Pimenta Dinis (Societies, 2021)
Worldwide, children and adolescents are exposed to violence every day and in countless contexts, whether in the family, at school, or in the community. Child multiple victimization has been the subject of extensive international research because of the impact on child and youth development. A quantitative and comparative study aiming to understand child multiple victimization and/or polyvictimization from the perspective of children is presented. Two groups were studied, with and without psychological counselling, with 20 children each, aged 12–18 years old. All the participants answered to juvenile victimization questionnaire (JVQ). The study was approved by the University Ethics Committee responsible for the study in Portugal, and it was initiated after the obtained consent of the children’s legal guardians. The results indicated that young people frequently experience violent situations, with particular emphasis on conventional crimes, e.g., theft, robbery, vandalism, and assault with or without a weapon, with sexual victimization being less common. The results also show that there is a cumulative experience of violence, which evidences multiple victimization and polyvictimization of the child/adolescent throughout their life. These phenomena are not necessarily more common between populations with clinical follow-up. When the types of violence were compared, multiple victimization and polyvictimization, this study found no differences between the samples with and without psychological counselling. It can be concluded that the multiple victimization or polyvictimization problem is not unusual among the population in the studied age range. It is important to alert to the phenomenon of child/adolescent multiple victimization, aiming at a more effective assessment and intervention among these populations. Raising awareness of the phenomenon of multiple child and youth victimization or polyvictimization is of particular importance for preventing violence at all stages of development.